REVIEWING RELIGIOUS UNDERSTANDING OF THE MARRIAGE HADITH - Nurul, Nurul; Khoiril Waro, Mochamad Tholib (RIWAYAH, 2022)
Intellectual discourse on women especially on marriage in Islamic tradition are dominated by patriarchal perspective. Islamic Intellectual treasures such as hadith and its explanation, exegesis, books, scholar and their intellectual products showed us how ancient Arabic patriarchal pattern existed. On the other hand, modernity led civilization to the values of equity, equality, human right and democracy against inequity, inequality, monarchy and individual cult. Problems of inequity appeared much on women discourse in Islamic tradition. Thousands of hadiths were identified recorded by men in patriarchal culture. It made gender issues in Islamic tradition are still sensitive. This article tries to reconstruct the discourse in one of the popular hadiths in marriage in order to explore the possibility of studying the meaning of a more moderate hadith.  By using Juynboll's common link, the author finds the hadith narrowed to one name, namely A'masy which is then categorized as a common link in this study.  In addition to having implications for the emergence of certain names as common links, this study also reviews further implications regarding the relevance of broader studies in hadith studies; urgent efforts to be made in order to place hadith as a source of more contextual and moderate religious discourse.[Tinjauan Pemahaman Agama Terhadap Hadis Pernikahan. Wacana intelektual tentang perempuan khususnya perkawinan dalam tradisi Islam didominasi oleh perspektif patriarki. Kekayaan Intelektual Islam seperti hadits dan penjelasannya, tafsir, kitab-kitab, ulama dan produk intelektualnya menunjukkan kepada kita bagaimana pola patriarki Arab kuno ada. Di sisi lain, modernitas membawa peradaban pada nilai-nilai kesetaraan, kesetaraan, hak asasi manusia dan demokrasi melawan ketidakadilan, ketidaksetaraan, monarki dan kultus individu. Masalah ketidakadilan banyak muncul pada wacana perempuan dalam tradisi Islam. Ribuan hadis diidentifikasi dicatat oleh laki-laki dalam budaya patriarki. Hal itu membuat isu gender dalam tradisi Islam masih sensitif. Artikel ini mencoba merekonstruksi wacana dalam salah satu hadis populer dalam pernikahan guna menjajaki kemungkinan mengkaji makna hadis yang lebih moderat. Dengan menggunakan common link Juynboll, penulis menemukan hadits tersebut dipersempit menjadi satu nama, yaitu A'masy yang kemudian dikategorikan sebagai common link dalam penelitian ini. Selain berimplikasi pada munculnya nama-nama tertentu sebagai common link, kajian ini juga mengkaji implikasi lebih lanjut mengenai relevansi kajian yang lebih luas dalam kajian hadis; Upaya mendesak dilakukan untuk menempatkan hadis sebagai sumber wacana keagamaan yang lebih kontekstual dan moderat.]